Sociolinguistics Etymologies of the Ewe Names Denoting the Relationship with Man and Animals - Horsu, Isaac; Akakpo, Imeta; Agbanyo, Wisdom Blackson (International Journal of Language and Literary Studies, 2025)
This work looks at the human-animal relation displayed in Ewe personal names in Ghana, Togo, and Benin by studying sociolinguistics and etymology. Using cultural and socio semiotic theories, the study adopted the qualitative method. This research reviews twenty animal-related Ewe names to find the cultural, symbolic, and spiritual reasons for their use. The study reveals that these names relate closely to shared memory and views, acting as markers of identity, values, and knowledge passed down through generations. Ewe animal-based names show totemic links, ecological awareness, moral lessons, and expectations. As such, they act as a linguistic link connecting language, environment, beliefs, and social structure. This study adds to African onomastics by showing how naming practices hold native ways of knowing and keep cultural heritage alive.